Longitudinal Follow-up of Children with Breakfast Consumption on Their IQ (P18-028-19). (13th June 2019) - Tien, Joyce; Um, Phoebe; Wu, Lezhou; Wang, Jessica; Pinto-Martin, Jennifer; Liu, Jianghong
Abstract: Objectives: Research has shown that regular breakfast consumption is associated with better cognitive functioning in children. However, most studies are cross-sectional, and measure either breakfast consumption or cognitive function at a single time point. In this 6-year longitudinal follow-up, we analyzed two phases of data collection to assess the effects of regular breakfast consumption at ages 6 and 12 on IQ and academic achievement. Methods: This longitudinal study is part of the China Jintan Cohort Study. While 1269 children participated in the study at age 6 and 835 children at age 12, 511 children had complete data in both phases of the study. Breakfast habits were assessed through parental questionnaires at age 6, and self-administered questionnaires at age 12. IQ tests at both ages 6 and 12 were conducted with the Chinese version of the Wechsler Intelligence Scale for Children. Multivariate mixed models were utilized to conduct repeated data analysis. Results: During the 6-year follow-up, 484 (94.7%) of 511 participants reported having breakfast ≥ 4 days per week ("always or often"), while only 27 (5.3%) children had breakfast ≤ 3 days per week ("sometimes or less"). After controlling for up to nine covariates, the longitudinal repeated analysis using multivariate mixed model showed that compared to less regular breakfast intake, regular breakfast consumption is associated with 5.537 points increased verbal and 4.349 points increased full IQ score (all P < 0.05). Further analysis utilizing the multivariate generalized linear model showed that children who regularly ate breakfast in either phase 1 or phase 2 were more likely to have higher verbal IQ scores (all P < 0.05) in contrast to their counterparts who did not regularly consume breakfast in either phase. Effects of all selected covariates were adjusted in this multivariate model. Conclusions: In this 6-year longitudinal follow-up of children who consistently eat breakfast at ages 6 and 12, we show that regular breakfast habits are associated with increasing IQ, particularly verbal IQ. Performance IQ was not significant. Further analysis is necessary to assess whether these effects translate into school performance and scholarly achievement. Funding Sources: National Institute of Environmental Health Sciences/National Institutes of Health (R01-ES-018858 K02-ES-019878 and K01-ES015877).